Instilling Character Values in Traditional Games in Elementary Schools - Mariatun, Mariatun; Sukarto, Sukarto; Hadi, Rusman (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Mariatun (2023). This research aims to find out whether traditional games can increase the value of honest character education and knowing the positives and negatives in elementary school. This qualitative research uses a phenomenological approach with descriptive methods. Data collection techniques in this research are observation, interview and documentation techniques. Interview. This research has several stages, namely data reduction, data presentation and drawing conclusions. To test the validity of the data in this research, the researcher used diligent observation and triangulation. The results of this research show that the value of honest character in traditional games and its impacts can be seen in the research results as follows: 1). Honest values in traditional games include: Obeying game rules, praying before playing, admitting mistakes in the game, reprimanding mistakes and apologizing to friends. The positive and negative impacts of the traditional Selodor game on the value of honest character include positive impacts, the costs required are low, develop children's gross motor skills, can develop social intelligence, they can use their free time by playing games which are very useful and the negative impact is that the Selodor game has risks. in the form of small fights, neglecting obligations when they are busy playing and feeling a little